Ethos discursivo e extimidade: uma análise da construção da imagem discursiva de divulgadores científicos no ecossistema Twitter - Redel, Alessandra (Universidade do Vale do Rio dos Sinos, 2023)
In 2020, because of the pandemic, several people joined social networks, mainly Twitter, in order to obtain information related to the disease – thus shedding light on science. Faced with this conjuncture, the ways of popularizing science needed to be reviewed and adapted to the new context. One of the novelties was the fact that many scientists used their own personal accounts on social networks to popularize science. The main objective is to verify how the image of scientific popularizers is constructed in the Twitter ecosystem, analyzing the presence of extimity discourse (fragments of intimacy with the aim of social validation) in the construction of the ethos. For this, we selected two profiles, Denise Garrett and Otavio Ranzani, epidemiologists who popularize science on Twitter, with great repercussions. The theoretical contributions that guide this research are the Theory of Digital Discourse, by Marie-Anne Paveau (2015, 2016, 2021), which deals with the specific characteristics of native digital discourses; and the postulates of Ruth Amossy (2005) and Dominique Maingueneau (2001, 2008, 2014, 2020) related to the studies of the discursive ethos. The type of the research is mixed (qualitative and quantitative), and the corpus of the study is composed of 128 screenshots, 4 of which are biographies (bios) of science popularizers, 82 are tweets published by Denise Garrett and 42 are tweets published by Otavio Ranzani, on their respective personal Twitter accounts. From the 128 captures, we chose to analyze those that best exemplify how the image of the promoters in question is built. The research findings indicate changes in the way of disseminating science and point to a new type of more humanized ethos of scientists and science popularizers.
Keywords: Divulgação da ciência; Discurso digital; Extimidade; Ethos discursivo; Twitter; Science popularization; Digital discourse; Extimacy; Discursive ethos; ACCNPQ::Lingüística, Letras e Artes::Lingüística